2021
DOI: 10.1186/s42492-021-00091-z
|View full text |Cite
|
Sign up to set email alerts
|

Acral melanoma detection using dermoscopic images and convolutional neural networks

Abstract: Acral melanoma (AM) is a rare and lethal type of skin cancer. It can be diagnosed by expert dermatologists, using dermoscopic imaging. It is challenging for dermatologists to diagnose melanoma because of the very minor differences between melanoma and non-melanoma cancers. Most of the research on skin cancer diagnosis is related to the binary classification of lesions into melanoma and non-melanoma. However, to date, limited research has been conducted on the classification of melanoma subtypes. The current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…The achieved accuracy for the Kaggle dataset was 88.95% and for the ISIC the accuracy was 90.96%. Abbas et al [ 33 ] introduced a custom build model for the classification of skin cancer based on the seven-layer of deep convolution network. The proposed model was trained from scratch.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The achieved accuracy for the Kaggle dataset was 88.95% and for the ISIC the accuracy was 90.96%. Abbas et al [ 33 ] introduced a custom build model for the classification of skin cancer based on the seven-layer of deep convolution network. The proposed model was trained from scratch.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers collected 724 dermoscopic images from AM patients and benign nevus (BN) patients for training and validation and created a seven-layered deep CNN for training from the self-collected dataset. This model achieves an accuracy of 97% with a custom-built deep ConvNet for AM, and the accuracy can be improved by using TL [28]. Similarly, Yang et al .…”
Section: The Application Of Ai In Melanomamentioning
confidence: 99%
“…Finally, another study showed that the anatomic site of a lesion plays a critical role in the performance of CNN [ 38 ]. Studies [ 18 , 39 41 ] have shown the potential of CNN-based classification for special anatomic sites—such as face, palms, and soles that have different normal dermoscopic signs—but more extensive and diverse datasets as well as further research are needed to extend the application of AI in rare anatomic sites (e.g., genital area) and rare skin cancer subtypes (e.g., mucosal or desmoplastic MM) [ 17 ]. On the other side, banal-looking, benign lesions such as angiomas, dermatofibromas, or nevi are most often underrepresented or absent from studies’ training sets, leading to underperformance of the algorithms [ 18 ].…”
Section: Pitfalls In Aimentioning
confidence: 99%